Study of Mechanical Properties of Reinforced Pineapple – Glass Fibers Epoxy Hybrid Composites - N Krishnarjuna Rao, G. S. Guru Dattatreya, E. Venugopal Goud (International Journal of Advanced Science and Technology, 2020)
Natural fiber-based compounds are being intensively studied due to their ecological nature and peculiar properties. The advantage of pineapple leaf fiber (PALF) is one of the raw materials available in abundance in India, relatively inexpensive and has the potential of a polymer-reinforced compound. In this work, pineapple fibers and glass fibers of different proportions, reinforced with epoxy resin, are prepared in the form of test samples recommended by ASTM. The application of mechanical load in test samples using Universal Testing Machine (UTM) mechanical properties are studied and analyzed, such as voltage strength, maximum load, young module of hybrid compound, stress and the folding module. The proportions considered for pineapple fiber and fiberglass are 8: 0, 6: 2, 4: 4, 2: 6, 0: 8. From research on these test samples, natural palf fiber, available in abundance in pineapple plants, can replace glass fibers up to 50-75% of the composition of the fiber, depending on the need for the application of mechanical properties.